(untitled) (Journal of Science and Technology, 2016)
A critical examination of the causes and effects of mathophohia was the focus of this paper. It was conducted among 300 secondary school students in a South-western town of Ile-Ife where Obafemi Awolowo University is situated. Data on causes and effects of mathophobia were collected using mathophobia questionnaire and mathematics results of two terms for the subjects used for the study. Four hypotheses were rested on the causes of methophobia, influence of mathophobia on career interest and achievement in mathematics and influence of mathophobia on students mathematics achievement in various subject groups. Data gathered were subjected to one-way analysis of variance and t-test. It was found out that mathophobia is caused by many factors which reveals that mathophobia could be innate and environment caused. It was also found out that students who have aspirations for non science related career are more mathophobic than those with interest in science and commercial related disciplines. Mathophobia was also found out to negatively affect students achievement in mathematics. This effect on achievement was found to vary among Science, Commercial and Arts students. All these results buttressed the existing findings in previous researches and support the trend of association between attitude towards mathematics and achievement in mathematics in the literature.